Contemporary Babon Angrem Batik Motif Design For Mitoni Traditional Cermination In Central Java - Theresia Widiastuti; Yosua Novalesi; Elizabeth Nimas Shaestu (Corak, 2022)
The life cycle ceremonies that symbolize the human journey are all found in traditional Javanese batik because in batik there is a symbol or meaning of life. At the age of 7 months of pregnancy, Javanese people usually hold a ceremony called mitoni, this ceremony is equipped with various ubo rampe, one of which is Babon Angrem batik. Changes in times including changes in cultural actors have caused many shifts in customs. This traditional ceremony began to be abandoned or become less complete due to economic factors. Individuals in this millennial era with modern perspective have witnessed a shrink of benefits of having traditional ceremonies. In response to this problem, the idea emerged to develop a long cloth with a millennial pattern that still adheres to the existing standard as a the mitoni ceremonial equipment. Batik is one of the assets that can be processed as a creative industry. By reprocessing and redefining the existing traditional motifs from today’s modern perspective, while maintaining the their originality. This design will certainly solve the problems of batik and tradition, to meet the  current style for the present generation. The Babon Angrem batik motif is applied on batik cloth to result in innovative products. The Babon Angrem batik motif, which is designed in a contemporary way, displays bright and warm colors that convey the a mother's love symbolized in the philosophical meaning of the Motif of Babon Angrem. The motifs of Babon Angrem include Babons ( hen) facing each other, hen laying eggs, ukel motifs that adorn all repetitions of Babon motifs, and ceceg which complete the background of this batik.